MODEL PENYELESAIAN PERKARA MENEMPATI TANAH TANPA IZIN YANG BERHAK ATAU KUASANYA DI TINJAU DARI HUKUM PIDANA - Razief Ardi Cahyo Sudarto; Hartanti Hartanti (Kajian Hasil Penelitian Hukum, 2022)
Research purposes To find out and analyze what factors influence the settlement of criminal disputes occupying land without the rightful permit or proxy Bantul Regency Subjective Goals To fulfill one of the requirements for obtaining a Master's degree Law at the University Janabadara Master's Faculty of Law Law Yogyakarta  To add to the library treasury in the form of a thesis at the Janabadara University library faculty of Law Master Law Yogyakartaresearch method used is as follows: The type of research used is normative juridical research. The normative research here is carried out by examining the object of the problem on the model of settlement of cases occupying land without the right of permission or their proxies in terms of the criminal aspect , which is based on the applicable legal provisions. The type of normative juridical research, namely research based on applicable laws and regulationsThe results of research and discussion, the authors conclude several things including the following: What factors influence the settlement of criminal disputes occupying land without the rightful permit or proxy? district Bantul criminal dispute occupying land without the rightful permission or their proxy district Bantul? Decision of the Bantul District Court Number 145/Pid.C/2018/PN Btl dated 22 November 2018 and subsequently adjudicated themselves; as follows; Stating that the act that was charged with Tukijah bint Hasan Abdul Gani alias Panggih the identity has been proven in advance, but the act does not constitute a crime To declare that the accused above is free from all legal charges, Restoring the rights of the defendant in his ability, position and dignity, Order evidence . The model of settlement of cases occupying land without the right of permission or their proxies is reviewed from criminal law and carried out outside the court. In this case it is termed penal mediation. The existence and implementation of penal mediation is outside the court